Photons Plus Ultrasound: Imaging and Sensing 2019 2019
DOI: 10.1117/12.2507446
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of a partially learned photoacoustic reconstruction algorithm

Abstract: Classical reconstruction algorithms for photoacoustic tomography (PAT) are mathematically proven to converge, but can be very slow and inadequate with respect to model and data assumptions. With the help of neural networks, learned reconstruction algorithms have recently been developed. These learned algorithms have shown to surpass the reconstruction quality of non-learned ones, but their mathematical analysis is challenging, therefore convergence and stability are not guaranteed. In this work, we combine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For reconstructions in PAT, the work by Boink et al [137][138][139] has demonstrated the robustness of these learned iterative schemes to a number of in silico phantoms as well as in an experimental study. The authors consider an extension to the learned gradient schemes introduced above called learned primal dual 18 (LPD) based on the successful primal-dual hybrid gradient method 140 (also known as the Chambolle-Pock algorithm).…”
Section: Learned Primal Dual In 2dmentioning
confidence: 99%
See 1 more Smart Citation
“…For reconstructions in PAT, the work by Boink et al [137][138][139] has demonstrated the robustness of these learned iterative schemes to a number of in silico phantoms as well as in an experimental study. The authors consider an extension to the learned gradient schemes introduced above called learned primal dual 18 (LPD) based on the successful primal-dual hybrid gradient method 140 (also known as the Chambolle-Pock algorithm).…”
Section: Learned Primal Dual In 2dmentioning
confidence: 99%
“…5(b). In their work, [137][138][139] the authors examined the robustness of LPD with respect to changes in the target, including the contrast, background, structural changes, and noise level. They found that if the network is trained only on the basic training data, it generalizes fairly well with respect to noise (1 dB degradation in PSNR) and structural changes (3 dB), but is most sensitive to changes in background (7 dB) and contrast (11 dB).…”
Section: Learned Primal Dual In 2dmentioning
confidence: 99%